Metagenomic Diversity of Gut Microbiota of Gestational Diabetes Mellitus of Pregnant Women - Minarti Minarti; Nurhidayat Triananinsi; Nurqalbi Nurqalbi; Sumarni Sumarni; Mudyawati Kamaruddin (Biomedika, 2020)
Gestational Diabetes Mellitus (GDM) is defined as a condition in which a woman without diabetes develops abnormal glucose tolerance that is first recognized during pregnancy. GDM is a significant public health problem with an incidence of 1.9 – 3.6% of all pregnancies in Indonesia. Additionally, women with GDM during pregnancy have a high risk of developing diabetes when they are not pregnant, such as type 2 diabetes (T2D). One alternative variable in the management of T2D globally is gut microbiota. Here, to find out the role of gut microbiota in pregnancy, we characterized the stools of 30 pregnant women, each consisting of fifteen GDM-detected pregnant women, and healthy pregnant women using metagenomic approach with genome analysis by directly isolating genomic DNA from the microbiota ecosystem that occupies the digestive tract. DNA sequencing results were analyzed by MEGA 6 software with the BLASTn algorithm in NCBI. Thus fifteen GDM-detected showed high nucleotide sequence homology with the Proteobacteria at phylum level, and Escherichia, Orchobacterium, Cronobacter, Shigella, Salmonella, Enterobacter, Klebsiella, Kosakonia, Vibrio dan Gamma-Proteobacterium at genus level compared to the healthy pregnant women which found by Firmicutes at phylum level and Ruminococcus, Clostridium, Clostridiales, Lachnospiraceae, Roseburia, Weisella, Eubacterium at genus level had a higher abundance in healthy pregnant women. In this result, we found also one of the fifteen healthy pregnant women showed differential abundance with enrichment of Prevotella species. Gut microbiota of GDM-diagnosed pregnant women has more varied composition, and dominated by the phylum Proteobacteria than in normal pregnant women.